Exploiting biological tools for post-antibiotic era: novel sustainable strategies against antimicrobial resistance - Omnia Karem Riad (Novel Research in Microbiology Journal)
Around the world, one of the biggest risks to public health is antimicrobial resistance (AMR). AMR poses substantial consequences on country economies and health systems. In the post-antibiotic era, searching for new cost-effective approaches is necessary to compensate for the continuous increase in AMR. The aims of this review are to explore the different biological and sustainable approaches that should be exploited to overcome the problem of AMR, discuss the mechanisms and advantages of different sustainable biological strategies, and introduce several strategies, including probiotic bacteria, predatory bacteria, and bacteriophages, which are powerful tools valuable to fighting resistant microorganisms with fewer chances of resistance development. Naturally synthesized products such as antimicrobial peptides and bacteriocins revealed successful treatment options. Additionally, the Clustered regularly interspaced short palindromic repeats (CRISPR-Cas) system is a gene-editing tool that can re-sensitize the resistant bacteria. Vaccination prevents infectious diseases and halts the emergence of resistant pathogens. Meanwhile, bacterial ghosts (BGs) and bacterial outer membrane vesicles (bOMVs) can be used to develop safe vaccines. bOMVs are also used as efficient tools for drug delivery due to their nanosizes. Additionally, antibody therapy and fecal microbial transplants are successful tools. Developing sustainable strategies to combat AMR through biological means looks promising. When compared to conventional antibiotics, these tactics have different mechanisms of action that may slow the emergence of antibiotic resistance.